Distribusi Barang dan Jasa dalam Perspektif Ekonomi Islam: Antara Keadilan dan Etika Syariah (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The distribution of goods and services is a vital component of the Islamic economic system, emphasizing the principles of justice, transparency, and divine blessings. In Islamic thought, distribution is not merely an economic activity but also a means to ensure social welfare and equitable asset ownership. This article explores the concept of distribution from an Islamic economic perspective based on sharia principles such as justice (`adl), trustworthiness (amanah), and the prohibition of usury (riba) and hoarding (ihtikar). Using a descriptive qualitative approach, this study analyzes relevant scholarly literature to understand the role of Islamic distribution channels in building an inclusive and fair economic system. It also highlights the influence of Islamic business ethics, maqasid al-shariah, and the concept of khalifah (stewardship) in promoting a distribution process that is just, transparent, and accountable. The findings reveal that Islamic distribution systems are not only economically efficient but also enriched with spiritual and social values rooted in justice and solidarity.